Inovasi Alat Penyortir Ikan Lele Guna Meningkatkan Efisiensi Waktu dan Kualitas Hasil Penyortiran di Peternakan Pak Arifin - Syah, Muhammad Althof Charies Rahman; Murnawan, Hery (Fakultas Teknik Universitas Tulang Bawang, 2025)
This study aims to develop an innovative catfish sorting tool to minimize the sorting process time at Pak Arifin's farm. The current sorting process takes up to 4 hours per session, potentially causing stress to the fish and physical fatigue to workers. This innovation includes an ergonomic tool design to reduce the risk of injury from improper working postures and adjustable sorting blades controlled by a lever. The tool is constructed using stainless steel for parts in direct contact with the fish to ensure hygiene and durability, while the frame is made of hollow iron to support structural strength. The implementation of this tool is expected to reduce sorting time by up to 50%, increase sorting capacity, and maintain the quality of sorted fish. Additionally, this tool significantly enhances worker productivity and comfort while meeting market demands for specific catfish sizes, ranging from 8 to 12 fish per kilogram. This research offers an innovative solution to improve operational efficiency in small to medium-scale aquaculture businesses Keywords: Catfish, Ergonomics, Productivity, Sorting Tool, Time Efficiency.